Penegakan Hukum Bagi Pelaku Cover Lagu Tanpa Seizin Pencipta Lagu - Cinta Annata Nurhan; Monica Maharani Dewi; Dania Maulinda; Tarisa Dinar Alifia; Syahrul Rizqi Ramadhan (Jurnal Hukum dan Sosial Politik, 2024)
Technology that is increasingly developing every time makes everyone can easily create works and can create songs easily. However, there are also musicians who commit violations by covering other people's songs without the permission of the creator. The results of the song cover are uploaded through the social media of the song cover owner as if they created the song. In this research the author formulates problems regarding law enforcement for the perpetrators of song covers without the author's permission. The author formulates the first regarding how the policy regarding the perpetrators of song covers on social media platforms without the permission of the songwriter? And secondly, does the policy accommodate and have legal consequences for café singers and social media singers? The method used by the author is normative legal research. The data collection uses data from primary legal materials The legal norms that apply in the national realm are written positive legal norms such as Law No. 28 of 2014 concerning Copyright and also books related to the theme of the writing. Policies on song covers on social media platforms without the author's permission vary depending on the copyright law in each country and the platform's policies. However, in general, song covers usually need to obtain permission from the song's copyright holder before they can broadcast or share their version. Some social media platforms have implemented systems that allow songwriters or copyright holders to claim content that uses their work. This means that cafe singers or social media singers may need to obtain permission or a license from the copyright holder before they can broadcast or share their version of a cover song. Cafe singers or social media singers should be aware of the copyright regulations that apply in their region and strive to comply with existing policies or obtain permission where necessary to ensure legal compliance and respect the rights of copyright holders.